1997
DOI: 10.1115/1.2819522
|View full text |Cite
|
Sign up to set email alerts
|

Wall Pressure and Effective Wall Shear Stresses in Heat Exchanger Tube Inlets With Application to Erosion-Corrosion

Abstract: Inclined flow into tube inlets is studied in order to identify flow characteristics associated with enhanced erosion-corrosion rates at tube inlets. Measured wall pressures and shear stresses are presented for inlet flow with inclination angles up to 60 deg for a tube Reynolds number of 71,000. These show that the areas with most potential for wear are located near the reattachment point of the recirculation bubble as well as in regions at the downstream side of the tube inlet. The latter are located opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This study uses an axisymmetric rig because of the improved flow symmetry compared to a two-dimensional set up [7], where the flow is inevitably characterized by a broad range of incidence angles. Initial velocity measurements in a circular duct without annulus proved very difficult near the duct center, because of vortex breakdown [14].…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses an axisymmetric rig because of the improved flow symmetry compared to a two-dimensional set up [7], where the flow is inevitably characterized by a broad range of incidence angles. Initial velocity measurements in a circular duct without annulus proved very difficult near the duct center, because of vortex breakdown [14].…”
Section: Experimental Approachmentioning
confidence: 99%
“…Elvery and Bremhorst [7] provide experimental data for the pressure and wall shear stress in the tube entrance region of a heat exchanger, placed at an incidence to the flow. The results show that the size of the recirculation region near the entrance grows for increasing values of a, from 0:5d for a ¼ 0 to about 2d for a ¼ 60 .…”
Section: Introductionmentioning
confidence: 99%
“…Their first evidence was detected from 100 g × L −1 and 50 g × L −1 for the jet angles of 90 • and 45 • . It is believed that these macroscopic surface deformations result from a modification of the local particle distribution and the average particle velocity due to the surface geometry modification and local fluid recirculation region on SM400B [10,67,68]. Cross-section observations were performed in the jet flow direction (45 • ) for samples eroded with 10 g × L −1 and 145 g × L −1 of particles.…”
Section: Erosion Corrosion Morphologiesmentioning
confidence: 99%
“…Studies conducted in recent years have suggested some possible mechanisms. A relevant study concerning tube inlet damage was published by Elvery (1995) and Elvery and Bremhorst (1997). The main hydrodynamic parameters under consideration were the wall pressure and wall shear stresses present in the tube inlets for varying inlet inclined flow conditions.…”
Section: Experimental Backgroundmentioning
confidence: 99%